Model combination and environmental adaptation for improved noisy speech recognition - Tan, Sang Sang, 1983-; Abd. Manan Ahmad (Skudai : Universiti Teknologi Malaysia, 2008)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2008